Ovarian steroid cell tumors: what do we know so far? - Wei, Christina H.; Fadare, Oluwole (Frontiers in Oncology, 2024)
Steroid cell tumors (SCT) of the ovary are rare, which has limited advances in the understanding of this enigmatic neoplasm. In this review, we summarize currently known clinicopathologic information on SCT. SCT are frequently hormonally active, leading to elevated serum and/or urine levels of androgenic hormones or their metabolites, and associated symptomatology, including virilization. The reported age at diagnosis is broad and has ranged from as young as 1 year old to 93 years old, although most patients were between ages 20 and 40 years. Most tumors are stage I and unilateral. The tumors are usually well circumscribed with a solid or solid to cystic cut surface. The tumors in one series reportedly ranged in size from 1.2 to 45 cm (average 8.4 cm). MRI is a useful imaging modality, typically showing a well delineated mass with contrast enhancement and lipid content on on T2 and T1 weighted images, respectively. Microscopically, SCT display polygonal to epithelioid cells with abundant eosinophilic to vacuolated/clear cytoplasm and display an immunoprofile that is consistent with sex cord-stromal differentiation. Most cases are benign, without any recurrences after primary resection, but a subsetprobably less than 20% of casesare clinically malignant. Pathologic criteria that can specifically predict patient outcomes remain elusive, although features that correlate with adverse outcomes have been proposed based on retrospective studies. The molecular characteristics of SCTs are similarly under characterized, although there is some evidence of an enrichment for hypoxia-signaling gene mutations in SCT. In malignant SCT, the tumors generally show greater global genomic instability, copy number gains in oncogenes, and occasional BAP1 mutation. Future studies involving multi-institutional cohort and unbiased molecular profiling using whole exome/transcriptome sequencing are needed to help advance our molecular understanding of SCTs.